Simulasi IoT Pemantauan Tanaman Lidah Buaya Berbasis Algoritma Fuzzy - Ramadhan, Bayu Yudistira; Putri, Luh Arida Ayu Rahning (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 1 (2024): JNATIA Vol. 3, No. 1, November 2024DO - 10.24843/JNATIA.2024.v03.i01.p22, 2024)
In the digital era, technological advancements have entered the Industrial Revolution 4.0, and the agricultural sector in Indonesia is adapting to this revolution. Using a fuzzy algorithm, this research simulates an IoT-based monitoring system for Aloe vera plants. The system aims to assist farmers in real-time and accurately monitor Aloe vera plant conditions. Aloe vera has a narrow optimal temperature range of 16-33°C and an ideal soil moisture range of 40-75% for optimal growth. By implementing fuzzy logic, a mathematical concept that is easy to understand, the system can accurately map input conditions to output decisions. The simulation uses MATLAB and the Tinkercad website to design a fuzzy logic system that controls a water pump and fan based on soil moisture and temperature inputs from SEN1 and LM35 sensors, respectively. The fuzzy rules maintain the ideal conditions for Aloe vera growth, reducing energy consumption and water waste. The results demonstrate the high accuracy of the fuzzy logic system in making control decisions for maintaining optimal growing conditions.